Analisis Kinerja Pemasaran UMKM Produk Olahan Singkong di Wilayah Lebak-Banten - Miguna Astuti; Tati Handayani (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
The purpose of this research To realize economic and social resilience, which is oriented towards poverty alleviation in the context of community welfare in the Lebak Regency, Banten, through product innovation analysis, Market Orientation, and Entrepreneurship orientation towards the MSME marketing performance of cassava processed products in the Lebak-Banten region. The research method used was a mixed-method, with a population of SMEs processed by cassava in the Cibadak area, Lebak, Banten. The number of respondents used was 72 respondents. Product innovation and entrepreneurial orientation do not affect marketing performance, but market orientation has significantly related to marketing performance. The MSMEs in Lebak Banten are not supported by inappropriate information technology. In this case, it is to improve the entrepreneurial orientation of the MSME actors by displaying all products that are sold either the same or not the same as the intended product so that consumers walk on their own to see the uniqueness said indirectly.